Construction on the Green function for Vallee-Poussin problem for nonlinear system of differential equations - Sobkovich, R.I.; Kazmerchuk, A.I. (Carpathian Mathematical Publications, 2013)
Existence and uniqueness theorems of solution of n-point Vallee-Poussin problem for system of nonlinear differential equations are proved. Iterative schemes for finding them are proposed.